PENERAPAN NAÏVE BAYES DALAM PROSES PENILAIAN KINERJA PEGAWAI KLINIK UTAMA BAITUL HIKMAH - Edy Siswanto (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2021)
Employee performance appraisal at Baitul Hikmah Main Clinic still uses the conventional method by filling out forms & manually calculated. The head of the unit assesses the performance of each of its members from aspects or competencies for which there are no assessment indicators determined. This makes unit to evaluate each of its members as a result the evaluation process is considered less effective and causes subjective evaluations and causes cases between employees, for employee assessment to facilitate performance appraisals. The author makes an employee performance appraisal application using the Naive Bayes method easier to provide performance appraisals.